A Glassy Carbon Electrode Modified by a Copolymer of Co-Tetrakis (Para-Aminophenyl)Porphyrin and Ortho-Phenylenediamine. Characterization and Electrocatalytic Sulfite Oxidation Behavior of a Basic Extract from Red Wine - Aguirre-Quintana, M; Aguirre-Quintana, M; Romero-Figueroa, J; Arce-Escobar, R; Arce-Escobar, R (Kluwer Academic Publishers, 2014)
In this work, we present a comparison among three glassy carbon electrodes modified by Co-porphyrin, ortho-phenylenediamine, or both simultaneously. This comparison shows the differences among the electrochemical behavior, morphological characteristics and electrocatalytic behavior toward the sulfite oxidation of these electrodes. The electrode modified by Co-porphyrin, ortho-phenylenediamine and copolymer has been investigated in detail for the comparision of electrocatalytic activity towards the sulfite oxidation. In the case of the glassy carbon-modified electrodes, the presence of the copolymer enhances the electrocatalytic performance of the modified electrodes in spite of the non-catalytic response (compared to the bare glassy carbon) of both homopolymer-modified electrodes toward the oxidation of sulfite. Additionally, the oxidation of sulfite extracted from red wine is shown. The copolymer-modified electrode is capable of oxidizing the extracted free sulfite in a 0.02 M NaOH solution. Through the addition of standards method, a concentration of free sulfite in a Chilean red wine sample was determined to be 44 ppm. © 2014, Springer Science+Business Media Dordrecht.